Applying grey theory to evaluate the effectiveness of integrating hands-on robotics into english remedial instruction for fourth-grade underachievers - Sheu, Ping-Huang (International Journal of Educational Technology and Learning, 2025)
This study explores the effectiveness of humanoid robots as instructional tools in remedial English education for elementary school underachievers. The integration of educational robotics into language instruction has attracted growing interest, yet its application in supporting low-achieving learners remains underexplored. Nineteen fourth-grade students identified as underachievers participated in a robot-assisted learning program aimed at improving their English language performance. The study employed the S-P chart and GSP chart analytical methods to examine students’ academic achievement and the relative difficulty of test items before and after the intervention. Analysis of the S and P curves revealed that the correct answer rate increased following instruction, with the test difficulty shifting to a moderate level. The caution index provided additional diagnostic insights into students’ learning conditions and the performance consistency of specific test items. Furthermore, the GSP chart indicated a general improvement in student academic achievement, even though the test difficulty remained unchanged. These findings suggest that robot-assisted instruction can support learning gains among elementary underachievers and highlight the value of grey system theory in tracking both student progress and instructional effectiveness. The study offers practical implications for integrating robotics into language education and demonstrates the potential of grey system theory as a diagnostic tool in educational assessment, particularly in designing interventions for students requiring additional support.